Government Spending and Real Exchange Rate Case of Albania - Cakrani, Edmira; Resulaj, Pranvera; Koprencka (Kabello), Luciana (European Journal of Sustainable Development, 2013)
Various studies have found that governmentspending can lead to overestimation orunderestimation of the real exchange rate, depending on the composition of theseexpenditures. The purpose of this paper is toassess the impact of government spendingon real exchange rate in Albania. In this paper is used a log liner model with quarterlydata. Other explanatory variables in this model are: foreign direct investment, remittances,real GDP per capita, openness. Variables are tested for unit root and cointegration. Theresults indicate that government spendingis associated with overvaluation of realexchange rate in Albania.JEL Classification: E62; F31Various studies have found that governmentspending can lead to overestimation orunderestimation of the real exchange rate, depending on the composition of theseexpenditures. The purpose of this paper is toassess the impact of government spendingon real exchange rate in Albania. In this paper is used a log liner model with quarterlydata. Other explanatory variables in this model are: foreign direct investment, remittances,real GDP per capita, openness. Variables are tested for unit root and cointegration. Theresults indicate that government spendingis associated with overvaluation of realexchange rate in Albania.